Growth of aligned ZnO nanorods array on ITO for dye sensitized solar cell - Yengantiwar, Ashish; Sharma, Ramakant; Game, Onkar S.; Banpurkar, Arun G. (Current Applied Physics, 2011)
Aligned ZnO films of nanorods arrays were grown on Indium doped Tin oxide (ITO) glass substrate for the Dye Sensitized Solar Cells (DSSCs) applications. Two-step approach was employed for the deposition, which offers advantages such as excellent surface adhesion, large area deposition, high reproducibility and yield. Structural characterization using X-ray diffraction (XRD) shows a preferred c-axis (002) oriented growth. Scanning Electron Microscopy (SEM) images reveals uniformly distributed hexagonal ZnO nanorods with average diameter varying from 80 to 250 nm. Average growth rate of the films was estimated using Surface Profilometer which was found to be similar to 1 mu m/h. Optical characterizations were carried out using Photo-spectrometer and Raman spectroscopy. The DSSCs using these ZnO films of nanorods array as photo-electrodes show conversion efficiency ranging from 0.24 to -0.71 %, the maximum efficiency was obtained for films deposited for time duration 8 h. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Aligned ZnO nanorod growth; Dye sensitized solar cell; Open aqueous solution deposition

Shape preserving chemical transformation of ZnO mesostructures into anatase TiO2 mesostructures for optoelectronic applications - Muduli, Subas; Game, Onkar S.; Dhas, Vivek V.; Yengantiwar, Ashish; Ogale, Satishchandra B. (Energy & Environmental Science, 2011)
In this work we report on the synthesis of various ZnO mesostructures (rods, spheres, flakes and flower-like morphologies) by hydrothermal and co-precipitation methods and their remarkable and complete transformation into anatase TiO2 mesostructures with nominally similar shapes using controlled low temperature TiCl4 treatment. Various techniques are used to demonstrate the phase purity and morphology details. Based on the careful examination of the transformation of ZnO rods into TiO2 tubes we suggest a mechanism which embodies initial formation of a thin TiO2 shell on the ZnO surface by ion exchange (Ti4+-Zn2+) followed by Zn diffusion through the shell and its oxidation on the surface. We used these converted TiO2 mesostructures for light harvesting in Dye Sensitized Solar Cells (DSSCs) to enhance the conversion efficiency. It is shown that DSSCs made using a doctor bladed film of TiO2 nanoparticles with an overlayer of TiCl4 treated ZnO flowers yield a solar cell efficiency of 6.9% which is considerably higher than that with only TiO2 nanoparticle film (5.4%) of comparable thickness.

Strong photo-response in a flip-chip nanowire p-Cu2O/n-ZnO junction - Deo, Meenal S.; Mujawar, Sarfraj; Game, Onkar S.; Yengantiwar, Ashish; Banpurkar, Arun G.; Kulkarni, Sneha; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Nanoscale, 2011)
Cu2O nanoneedles are synthesized on a copper substrate by a simple anodization and reducing ambient annealing protocol. ZnO nanorods are grown on ITO coated glass by a low temperature chemical route. The electronic and photo-response properties of the p-Cu2O/n-ZnO flip-chip heterojunction are then studied and analyzed. We show that the I-V characteristic is rectifying and the junction exhibits a good photoresponse (similar to 120% under 1 V reverse bias) under AM 1.5 (1 Sun) illumination. This nano-heterojunction photo-response is far stronger as compared to that of a pulsed laser deposited thin film p-Cu2O/n-ZnO heterojunction, which can be attributed to higher junction area in the former case.

Growth of Mo-doped Ni3S2 nanorods array for superior overall water splitting reaction - Sharma, Pooja; Khandare, Lina; Saha, Arindam; Chaure, Nandu B.; Yengantiwar, Ashish (International Journal of Hydrogen Energy, 2025)
Designing novel, efficient and cost-effective dual-functional electrocatalyst for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) using an alkaline electrolyte is crucial for establishing a sustainable hydrogen economy and transitioning to a society powered by renewable energy sources. In the present work, Mo-doped nickel sulfide (Mo-Ni3S2) nanorods were grown on Ni-treated nickel foam (N-NF) substrate via a two-steps hydrothermal method. Specifically, Mo-Ni3S2/N-NF surface consists of nanorods-like morphology, which provides extensive area for percolation of electrolyte, that resulting in outstanding catalytic performance. Such a well-synthesized electrode exhibited superior performance and stability for OER as compared with pristine Ni3S2/NF and bare nickel foam (NF) electrodes. In addition, Mo-Ni3S2/N-NF electrode provides good HER activity and confirms its dual-functionality in alkaline medium. Our champion Mo-Ni3S2/N-NF electrocatalyst delivers best OER overpotential of 230 mV at current density of 100 mA/cm(2). Also, it provides HER overpotential of 100.6 mV at a current density of 10 mA/cm(2). Both OER and HER are carried out in the presence of 1 M KOH alkaline electrolyte. OER stability of the best-performed Mo-Ni3S2/N-NF electrode demonstrates almost constant current density similar to 120 mA/cm(2), which retains 90% of original value after continuously tested for the duration of 22 h. The total cell voltage of 1.56 V is provided by Mo-Ni3S2/N-NF integrated system and it demonstrates a good stability for duration of 22 h. Our approach provides a new insight into developing earth-abundant, inexpensive and superior dual-functional electrocatalyst for overall water splitting reaction (WSR).
Keywords: Dual-functional electrocatalyst; HER; Mo doping; Nickel sulfide nanorods; OER; overall water splitting